Entrepreneurs' education: Critical areas for the pedagogic‐didactic agenda and beyond - Grüner, Herbert; Neuberger, Lars (Journal of Business Economics and Management, 2006)
In the following article we aim to give the reader an insight into the problems we have encountered since we began developing a curriculum for entrepreneur education at university level. We have been able to find solutions to some of the problems faced. More interesting though seem to be the quandaries which crop up almost automatically when pedagogues attempt to formulate a programme of “Entrepreneur Education”. They give us occasion to critically reflect on some accepted standpoints, and should also open up interesting perspectives for the reader for his or her own consideration. As such we intend to spend more time on the quandaries whilst providing rather brief sketches of our solutions. We hope to be able to offer a small contribution to the field in order to fuel critical debate in the discipline of Entrepreneurship Research and Education; debate whose aim is to effect critically constructive reflection on practice and existing knowledge, and forge innovative new paths towards the object of research.Firstd Published Online: 14 Oct 2010